Scope of Interpretive Attitudes - Muhammad Qurbanzadeh; Muhammad Hasan Rostami (آموزه‌های قرآنی, 2012)
Each of the commentators of the Holy Quran has interpreted it so that great variation in their interpretative books and their writings has occurred. Now the question is that to what extent this variation is permissible and how much it can be extended? Given to the semantic distinction between interpretive approaches and trends that will be discussed, it seems that the development of interpretive trends is more possible than interpretive methods. Commentators have had much speech in this field and have created considerable diversity in the interpretive writings. It can also be said that the range of variation depends on the needs and scientific findings of commentators and regarding interpretive rules. This article has provided a new vision in the field of interpretive trends and necessity of separation between methods and attitudes.